Enhancing Democratic Participation with Biometric and Technology-Based Voting Systems - Manimaran, S.; Sheriff, Akbar; Sufiyan, T. Muhammed; Anwar, S. Syed; Ali, M. Mohamed Sameer; Maricar, J. Mohamed Zakkariya; Suhail, A. Mohamed (Central Asian Journal of Medical and Natural Science, 2025)
Free elections are the most important part of democracy. People use elections to confirm their opinions and voices and choose someone whose ideas they agree with the most. Elections will let voters choose their representatives. The elections are not only to choose the winner, but also to give the winner credibility among voters who did not vote for them. This stresses the need of having free, fair, and secret elections. It means that independent, fair, and responsible electoral bodies are in charge of overseeing elections. The saying "today’s teens, tomorrow’s citizens" means that students should be involved with, trained for, and familiar with the election process. In this way, colleges and universities organize general elections for their student governments. This student will learn firsthand how to file nominations, check papers, withdraw, canvass, address, and, most importantly, vote. Voting with technology will be easier, more effective, and less likely to be hacked. Technology will make all votes safer and faster, making counting and automatic verification far more useful. It is hard to make a better voting system because there are so many important things that need to be done. It is important to keep the poll secret. There should be no way to tell which candidate obtains a certain vote in the voting mechanism. The authors used the Authenticated Voting Machine in the elections talked about in this work to make things easier and more open. The idea is still quite new. More study is needed to make it stable and theoretically sound. The model uses radio frequency and fingerprint recognition, as well as an OT-based system, to keep things safe.